Advance in identified targets of berberine - Sun, Penghai; Wang, Ziyuan; Ma, Yinchao; Liu, Yuan; Xue, Yintong; Li, Yan; Gao, Xiang; Wang, Yuedan; Chu, Ming (Frontiers in Pharmacology, 2025)
Berberine is an isoquinoline alkaloid, which has demonstrated significant therapeutic potential in the treatment of various diseases, including tumors, acute and chronic infections, autoimmune disorders, and diabetes. Studies have demonstrated that berberine exhibits polypharmacological effects, including antibacterial, anti-inflammatory, antioxidant, and hypoglycemic activities. To further elucidate the multifaceted pharmacological mechanisms of berberine, we reviewed 7 targets of berberine identified through co-crystal structure analysis, including filamentous temperature-sensitive protein Z (FtsZ), QacR, BmrR, phospholipase A2 (PLA2), RamR, NIMA-related kinase 7 (NEK7), and mesenchymal-epithelial transition (MET). Through target fishing, molecular docking, and surface plasmon resonance (SPR) analyses, combined with cellular and molecular experiments, we further identified 6 targets of berberine. These findings provide a comprehensive summary of berberine’s direct molecular targets, offering a theoretical foundation for further exploration of its diverse pharmacological activities.